Can we constrain a cosmological magnetic field via network analysis? - Rudakovskyi, Anton; Tsizh, Maksym; Vazza, Franco (Astronomy and Space Physics in Kyiv University, 2025)
The nature of magnetic fields detected on scales of galaxy clusters remains uncertain. Astrophysical mechanisms that generate magnetic fields often struggle to describe the observed field strengths, making scenarios involving primordial magnetic fields (PMFs) particularly appealing. In such models, the additional pressure generated by magnetic fields can influence the formation of low-mass galaxies and affect their distribution within the cosmic web. In this work, we present a novel suite of magneto-hydrodynamical simulations, MAKITRA, designed to investigate the effects of PMFs on the structure of the cosmic web. We model the distribution of galaxies in the simulations as a network and apply innovative methods of network analysis. Our results demonstrate that various network metrics can serve as sensitive probes of primordial magnetic fields at the nanogauss (~nG) level. These metrics offer constraints on PMFs that are comparable to those derived from Cosmic Microwave Background (CMB) observations.